SMAD4 loss enables EGF, TGFβ1 and S100A8/A9 induced activation of critical pathways to invasion in human pancreatic adenocarcinoma cells - Moz, Stefania (Oncotarget, 2016)
Epidermal Growth Factor (EGF) receptor overexpression, KRAS, TP53, CDKN2A and SMAD4 mutations characterize pancreatic ductal adenocarcinoma. This mutational landscape might influence cancer cells response to EGF, Transforming Growth Factor β1 (TGFβ1) and stromal inflammatory calcium binding proteins S100A8/A9. We investigated whether chronic exposure to EGF modifies in a SMAD4-dependent manner pancreatic cancer cell signalling, proliferation and invasion in response to EGF, TGFβ1 and S100A8/A9. BxPC3, homozigously deleted (HD) for SMAD4, and BxPC3-SMAD4+ cells were or not stimulated with EGF (100 ng/mL) for three days. EGF pre-treated and non pretreated cells were stimulated with a single dose of EGF (100 ng/mL), TGFβ1 (0,02 ng/mL), S100A8/A9 (10 nM). Signalling pathways (Reverse Phase Protein Array and western blot), cell migration (Matrigel) and cell proliferation (XTT) were evaluated. SMAD4 HD constitutively activated ERK and Wnt/β-catenin, while inhibiting PI3K/AKT pathways. These effects were antagonized by chronic EGF, which increased p-BAD (anti-apoptotic) in response to combined TGFβ1 and S100A8/A9 stimulation. SMAD4 HD underlied the inhibition of NF-κB and PI3K/AKT in response to TGFβ1 and S100A8/A9, which also induced cell migration. Chronic EGF exposure enhanced cell migration of both BxPC3 and BxPC3-SMAD4+, rendering the cells less sensitive to the other inflammatory stimuli. In conclusion, SMAD4 HD is associated with the constitutive activation of the ERK and Wnt/β-catenin signalling pathways, and favors the EGF-induced activation of multiple signalling pathways critical to cancer proliferation and invasion. TGFβ1 and S100A8/A9 mainly inhibit NF-κB and PI3K/AKT pathways and, when combined, sinergize with EGF in enhancing anti-apoptotic p-BAD in a SMAD4-dependent manner.